Initiatives citoyennes de transition soutenable et diffusion : formes et fonctions de la mise en réseaux territorialisés - Nassima Hakimi Pradels; Jean-Baptiste Grison; Kirsten Koop; Pierre-Antoine Landel (Développement Durable et Territoires)
Citizens' initiatives for sustainable lifestyles have been multiplying all over Europe since the beginning of the 21st century. The literature emphasises that they bear visions, values and practices which slightly differ from the dominant societal model. Nevertheless, the crucial question of the capacity of such local initiatives to transform territories on a larger scale has not yet been addressed. In this article, we start with the hypothesis that the consolidation and dissemination of alternative values and practices within territories depends on the weaving of links between the actors of alternative projects and their networking. Based on the results of research on citizen initiatives in the Northern Alps and the Massif Central, this article highlights the forms and functions of such territorialized networks.